Analysis of digital-based marketing strategy in supporting business activities of young entrepreneurs - Riswandi Paradi; Rahmad Solling Hamid; Goso Goso; Imran Ukkas (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This research aims to formulate a digital-based marketing strategy for young entrepreneurs. This study uses a qualitative approach through an interpretive paradigm by adopting a marketing mix. The population used in this study is the entirety of young entrepreneurs between the ages of 25 and 40 years in North Luwu. The minimum sample size was taken based on the calculation of 10 times the number of measurement items and obtained a total sample of 183. The analytical method used to formulate a digital-based marketing strategy is SWOT (Strength, Weakness, Opportunity, Threat) analysis. Before this analysis stage, the data quality test was first carried out, namely the validity and reliability tests. This study resulted in nine formulations of digital-based marketing strategies to support the business activities of young entrepreneurs, namely three strategies (S-O), two strategies (S-T), two strategies (W-O), and two strategy formulations (W-T).